Potential Danger of Structural, Building and Finish Materials of Objects Examined by Mobile Diagnostic Groups as Part of Chemical Control - J. V. Tkachuk; M. P. Shabelnikov; A. V. Ternovoy; S. A. Tkachenko; Y. P. Savinkov; E. A. Vasilkova (Вестник войск РХБ защиты)
The implementation of chemical control in closed facilities is the most difficult task of the mobile diagnostic groups (MDG) of the NBC Protection Troops of the Armed Forces of the Russian Federation, designed to perform radiation, chemical and biological control at mass events at national and international levels. Built with the use of modern construction and finish materials, they have their own sources of indoor air pollution. In certain cases, the use of polymer and polymer-containing materials in the construction and decoration of such objects leads to the appearance of contamination zones inside these premises with a high concentration of chemical impurities and their transformation products, which poses a threat to human health and affects the reliability of the results of chemical control. The last factor poses the greatest danger, since, leading to an inadequate reaction of the chemical control equipment, it can mask the appearance of poisonous and / or hazardous substances in the air, nullifying the entire complex of measures to ensure chemical safety. The aim of the article is to analyze structural, building and finish materials used in the construction and decoration of facilities that are systematically examined by MDG for the detection of toxic volatile compounds. It is shown in the article, that in the presence of sources of volatile substances, including toxic ones, which can distort the results of chemical control at the surveyed objects, it is necessary to improve the equipment and methodological support of mobile diagnostic groups.